The Effectiveness of Training Interventions in the Enhancement of Youth Entrepreneurial Skills and Knowledge - MNCWANGO, Sinqobile Immaculate; ADANLAWO, Eyitayo Francis (Journal of Posthumanism, 2025)
Youth unemployment is an ongoing issue that affects individuals domestically and globally, such a problem has been an issue for several years, which indicates that youth entrepreneurship as an initiative is imperative. Schumpeter’s theory of innovation serves as a theoretical foundation for the study. To investigate the effectiveness of training interventions in the enhancement of King Cetshwayo District youth entrepreneurial skills and knowledge, the study adopted a survey interview. 18 participants from the Zululand Chamber of Commerce and Industry (ZCCI), Youth Business Advisory Centre (YBAC), and the Small Enterprise Development Agency (SEDA) were interviewed. To analyse the collected data, NVIVO version 12 and Microsoft Excel were used. The findings revealed that the entrepreneurial capacity development programmes were effective in enhancing youth skills and knowledge. The study also uncovered that the effectiveness of the programmes enhanced business skills and acumen and improved youth business outcomes and success. The study recommends, among other things, the establishment of a tracking tool or system, since agencies reported that they do not have a tool used to track progress on business ventures of previously engaged young entrepreneurs. The practical implication of this study is that it can serve as a guideline for local government on the allocation of resources for youth capacity-building initiatives.